The benefits of green roofs for urban water management and thermal regulation: Insights from Catania (Sicily, Italy) - F. Licciardello; L. Sciuto; S. Cascone; V. Scavera; S. Vitaliano; G. Longo-Minnolo; T. Rizzo; S. Consoli; G.L. Cirelli (Ecological Engineering, 2026)

Long term performance of Nature-Based Solutions as decentralized wastewater treatment: a case study of a retail store in southern Italy - F. Licciardello; S. Barresi; A. Marzo; A. Rizzo; L. Sciuto; D. Ventura; G.L. Cirelli (Ecological Engineering, 2025)

The role of Nature-Based Solutions for the water flow management in a Mediterranean urban area - L. Sciuto; F. Licciardello; V. Scavera; D. Verde; E.R. Giuffrida; G.L. Cirelli (Ecological Engineering, 2024)

Giant reed from wetlands as a potential resource for biomethane production - L. Sciuto; F. Licciardello; A.C. Barbera; G. Cirelli (Ecological Engineering, 2023)

Preliminary data on ostracods and foraminifers living on coralligenous bioconstructions offshore Marzamemi (Ionian Sea, SE Sicily) - F. Sciuto; C. Altieri; D. Basso; F. D'Alpa; G. Donato; V.A. Bracchi; M. Cipriani; A. Guido; A. Rosso; R. Sanfilippo; D. Serio; A. Viola (Revue de Micropaléontologie, 2023)

New Mediterranean Biodiversity Records (November, 2016) - CH. MYTILINEOU; E.H.Kh. AKEL; N. BABALI; P. BALISTRERI; M. BARICHE; Y.Ö. BOYACI; L. CILENTI; C. CONSTANTINOU; F. CROCETTA; M. ÇELİK; H. DERELI; C. DOUNAS; et al. (Mediterranean Marine Science, 2016)
In the present Collective Article information on 26 taxa belonging to 8 Phyla and extended from the western Mediterranean to the Levantine Sea are presented. The new records were found in 9 countries as follows: Spain: first record for the Mediterranean of the crab Cancer bellianus; Algeria: further records of the alien fish Lagocephalus sceleratus to the west Algerian waters; Italy: first report on the presence and establishment of the ctenophore Mnemiopsis leidyi in Lessina and Varano Lagoons (W. Adriatic) and of Penaeus aztecus in Corigliano Gulf (Italian Ionian). Moreover, the extension of the distribution range of the polychaete Branchiomma bairdi to W. Sicily as well as that of the crab Ocypode cursor and the bryozoan Catenicella paradoxa to E. Sicily are cited. Slovenia: the record of the rare saccoglossan gastropod Placida cremoniana from Piran (Gulf of Trieste) is the first for the Adriatic; Greece: the native sea slug Eubranchus farrani is the first from the Eastern Mediterranean; many sightings of the bamboo corals Isididae distributed along all the E. Ionian Sea and the establishment of P. aztecus in all Greek waters are also reported for first time; the westernmost extension of the alien urchin Diadema setosum in Cretan waters is cited and new sights of the alien species Goniobranchus annulatus and Pterois miles are shown. Turkey: the alien fish Champsodon capensis is reported for first time from the Aegean Sea and the native acari Agauopsis microrhyncha from the Levantine Sea; a new observation of the alien crab Atergatis roseus in Güllük Bay-Aegean is also mentioned; Cyprus: first records of the alien urchin D. setosum and Lobotes surinamensis in Cypriot waters; Lebanon: several sightings of Monachus monachus from the Lebanese waters indicate a potential better status of the species in the area, Egypt: first records of the alien crab Dorippe quadridens and the alien gastropods Nerita sanguinolenta and Conomurex persicus from the Mediterranean Egyptian waters; extension of the distribution range of Diodora funiculata and Diodora rueppellii and a second record of the alien Nerita sanguinolenta in the same area.

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

TM4SF1: a tetraspanin-like protein necessary for nanopodia formation and endothelial cell migration - Andrew Zukauskas; Anne Merley; Dan Li; Lay-Hong Ang; Tracey E. Sciuto; Samantha Salman; Ann M. Dvorak; Harold F. Dvorak; Shou-Ching Shih Jaminet (Angiogenesis, 2011)

Methicillin resistance and vancomycin heteroresistance in Staphylococcus aureus in cystic fibrosis patients - V. Cafiso; T. Bertuccio; D. Spina; F. Campanile; D. Bongiorno; M. Santagati; A. Sciacca; C. Sciuto; S. Stefani (European Journal of Clinical Microbiology & Infectious Diseases, 2010)